Analisis Kebutuhan Konsultasi Luka Berbasis Aplikasi Smartphone pada Luka - Ramdan, Mardiana Mochamad; Suryati, Yati; Santoso, Budi; Nurlina, Fitri (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the need for smartphone-based wound consultation among patients with wounds. The method used is a qualitative approach through focus group discussions (FGD) involving two groups of participants, namely six wound practitioners and nine wound patients. The results of the study showed that there were four main themes identified from the wound practitioner group, namely: (1) the concept of wound assessment, (2) the implementation of wound assessment, (3) the wound consultation process, and (4) the need for innovation. Meanwhile, the wound patient group identified themes such as: (1) difficulties in accessing information, (2) sources of information, (3) decision making in wound care, and (4) the need for application-based consultation. The conclusion of this study is that both wound practitioners and wound patients need innovation in the form of application-based consultation to facilitate remote consultation, increase access to expert care, and improve patient outcomes. Keywords: Smartphone Application, Wound Consultation, Wound Patients